A Fresh Look at Potential Output in Central, Eastern, and Southeastern European Countries - Podpiera, Jiri (IMF Working Papers; Working Paper ;, 2017)
Was the postcrisis growth slowdown in Central, Eastern and Southeastern Europe (CESEE) structural or cyclical? We use three different methods-production function approach, basic multivariate filter, and multivariate filter with financial frictions-to evaluate potential growth and output gaps for 18 CESEE countries during 2000-15. Our findings suggest that potential growth weakened significantly after the crisis across most countries in the region. This decline appears to be largely due to stagnant productivity and weaker capital accumulation, which were associated with common external factors, including trading partners' slow potential growth, but also decline in global trade and stalled expansion of global value chains. Our estimates suggest that output gaps in 2015 were largely closed in many countries in the region.